Theme: Higher education in the Philippines: From the Revolution to the 21st century (Không nhà xuất bản, 2020)
The Philippines’ centennial celebration of its independence as a nation was an auspicious occasion to take stock of the State of higher education in the country, to look back at the past and derive inspiration from its major achievements, and to look toward the future to find out what challenges should be tack- led to enable institutions of leaming to contribute to the attainment of the countrys developmental goals. Thus, the Commission on Higher Education decided to convene the nations education leaders at a National Centennial Congress on Higher Education on May 28-29, 1998, at the Manila Midtown Hotel in Ermita, Manila. The congress showed that the last 100 years of Philippine history provide us with a rich source of inspiration for maintaining the time-honored traditions, values an_ideals which enabled the countrys leaders, who were mostly products of the countrys higher education institutions, to achieve their lofty goals in the fìght for Philippine independence